Pengaruh Struktur Kepemilikan dan Ukuran Perusahaan terhadap Kinerja Keuangan pada Perusahaan Manufaktur Sektor Barang Konsumsi - Nathanael, Vivian Novita; Paramitha, Melvie (Prodi Akuntansi FEB UNITOMO, 2024)
The financial condition of a company over a certain period is referred to as financial performance, encompassing how funds are circulated and allocated to achieve the company’s objectives. This study is aimed at examining how ownership structure and company size impact the financial performance of consumer goods manufacturing companies incorporated in the Indonesia Stock Exchange from 2018 to 2022. Quantitative data is utilized in this research, with secondary data derived from the annual financial reports of companies listed on the Indonesia Stock Exchange (IDX). Data analysis is conducted using IBM SPSS Version 26. The research findings indicate that ownership structure has a positive and significant impact on financial performance, with a significance value of 0.010 < 0.05. Meanwhile, company size has a negative and significant impact on financial performance, with a significance value of 0.000 < 0.05. Keywords: Financial Performance, Ownership Structure, Company Size, Manufacturing Companies, Consumer Goods.